Visual and Linguistic Strategy: A Multimodal Analysis of PSI’s Political Posters - Sriwahyuni, Endang (CV. Era Digital Nusantara, 2024)
The study focuses on two PSI's political posters. It aims to analyze some political posters made for the campaign of the election. The posters were chosen randomly. The visual devices are analyzed using Kress and van Leeuwen’s model. A political discourse approach by van Leeuwen is adopted to identify the main discourse strategies to persuade people, especially young people, to vote in a specific way. The result shows that the posters use visual and linguistic strategies to convey a political discourse and to persuade the young audience to vote—the background of the posters, colors, body language, and facial expressions. The written text used in the poster is also effectively structured to represent the party’s ideologies and the candidate.